2016
DOI: 10.3390/polym8020030
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Polysaccharide-Based Nanoparticles: Preparation and Applications for Drug Delivery

Abstract: Abstract:In recent years, there have been major advances and increasing amounts of research on the utilization of natural polymeric materials as drug delivery vehicles due to their biocompatibility and biodegradability. Seaweed polysaccharides are abundant resources and have been extensively studied for several biological, biomedical, and functional food applications. The exploration of seaweed polysaccharides for drug delivery applications is still in its infancy. Alginate, carrageenan, fucoidan, ulvan, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(71 citation statements)
references
References 182 publications
(228 reference statements)
1
70
0
Order By: Relevance
“…Cellulose has three reactive hydroxyl groups, whereas seaweed has hydroxyl, carboxyl and sulphate groups [5,111]. Therefore, cellulose readily interacts with seaweed by forming hydrogen bonds.…”
Section: Compatibility Between Seaweed Andmentioning
confidence: 99%
“…Cellulose has three reactive hydroxyl groups, whereas seaweed has hydroxyl, carboxyl and sulphate groups [5,111]. Therefore, cellulose readily interacts with seaweed by forming hydrogen bonds.…”
Section: Compatibility Between Seaweed Andmentioning
confidence: 99%
“…The cell walls present in seaweeds are composed of polysaccharides. These polysaccharides mainly consist of small sugar units linked via glycosidic bonds, which have hydrophilic surface groups such as carboxyl, hydroxyl, and sulfate groups [80]. Typical polysaccharides found in seaweeds include agar, alginate, carrageenan, fucoidan, and laminarin [81].…”
Section: Biosynthesis Of Nanoparticlesmentioning
confidence: 99%
“…Since, most of these polysaccharides carry specific charges, they can be exploited in designing of mucoadhesive drug delivery system involving interactions with mucin. Among seaweed polysaccharides, alginates and carrageenans are extensively studied biopolymers for diverse applications in nanotechnology with positive outcomes with respect to particle size distribution, high drug incorporation efficiency, controlled drug release profile, easy penetration into target sites and biocompatibility paving the way for safe and effective drug delivery (Venkatesan et al, 2016;Rydahl et al, 2017). In the recent years, several studies have been reported on the use of fucoidan, ulvan and mauran as nanotechnology platforms, some of which are being discussed in very brief.…”
Section: Marine Sulfated Polysaccharides As Bionanotechnology Platformsmentioning
confidence: 99%